Drinking beyond the binge threshold in a clinical sample of adolescents. (15th February 2020) - Creswell, Kasey G.; Chung, Tammy; Skrzynski, Carillon J.; Bachrach, Rachel L.; Jackson, Kristina M.; Clark, Duncan B.; Martin, Christopher S.
Abstract: Background and aims: Nearly all the research conducted on high‐intensity drinking has focused on college and school‐based samples, with recent calls for research to understand this risky drinking pattern in non‐school‐based samples and across time. This study aimed to characterize predictors and consequences of non‐binge drinking, age‐ and gender‐adjusted binge drinking (level I) and drinking at levels representing two or more times (level II) and three or more times the level I binge threshold (level III) in a clinical sample of adolescents followed into young adulthood. Design: Cross‐sectional associations between non‐binge drinking, binge levels, and negative alcohol‐related consequences were examined during adolescence; prospective analyses tested whether adolescent non‐binge drinking and binge levels predicted alcohol use disorder (AUD) symptoms in young adulthood and whether changes in drinking motives over time were associated with binge levels in young adulthood. Setting: US clinical settings. Participants: A total of 432 adolescents (aged 12–18 years) with alcohol‐related problems followed into young adulthood (aged 19–25 years). Measurements: Life‐time drinking history, Structured Clinical Interview for DSM AUDs, and Inventory of Drinking Situations. Findings: Results were generally consistent with a distinction between binge level I versus levels II–III on various negative alcohol‐related consequences in adolescence ( P s < 0.05) that were maintained in young adulthood ( P s < 0.01). The maintenance of relatively high endorsement of enhancement and social motives over time was associated with binge levels II–III in young adulthood ( P s < 0.001); decreases in coping motives were associated with less risky drinking in adulthood ( P  = 0.003). Conclusions: Among US adolescents with alcohol‐related problems who were followed‐up in young adulthood (aged 19–25 years), standard threshold binge drinking (five or more drinks per occasion; level I) was generally associated with fewer alcohol‐related consequences and problem behaviors than binge drinking at two or more times (level II) or three or more times (level III) the standard binge threshold.